O trabalho por plataforma digital: o caso dos motoristas da Uber - Fonseca, Wagner de Sousa (2020)
The following study elaborates on digital platforms as labor management tools typical of the current phase of capitalism in the Digital Era, which promote the overvaluing of flexibility while structuring work on a completely on-demand basis. The investigation aims to analyze the labor relation established between the Uber company and the drivers registered in their platform of private transportation mediation, in the city of Natal/RN, over the period of four years between 2016 and 2020. The initial premise was that workers in this labor dynamic would assimilate the values related to the ideology of entrepreneurship to the point of not perceiving themselves as submitted to Uber. The research relied on semistructured interviews as a means of obtaining primary data with the colaborating subjects, as well as a vast bibliographical research on literature pertaining to the evidenced themes. We were able to verify that uberized workers confuse the flexibility of setting your own working hours to the freedom of a worker with no boss. This idea is reinforced by the company through its publicity ads, which portray their workers as partners with full autonomy to pick the days and times when they wish to work.